Resistant starch in cassava products - Pereira, Bruna Letícia Buzati [UNESP]; Leonel, Magali [UNESP] (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2014)
Found in different foods, starch is the most important source of carbohydrates in the diet. Some factors present in starchy foods influence the rate at which the starch is hydrolyzed and absorbed in vivo. Due the importance of cassava products in Brazilian diet, the objective of this study was to analyze total starch, resistant starch, and digestible starch contents in commercial cassava products. Thirty three commercial cassava products from different brands, classifications, and origin were analyzed. The method used for determination of resistant starch consisted of an enzymatic process to calculate the final content of resistant starch considering the concentration of glucose released and analyzed. The results showed significant differences between the products. Among the flours and seasoned flours analyzed, the highest levels of resistant starch were observed in the flour from Bahia state (2.21%) and the seasoned flour from Paraná state (1.93%). Starch, tapioca, and sago showed levels of resistant starch ranging from 0.56 to 1.1%. The cassava products analyzed can be considered good sources of resistant starch; which make them beneficial products to the gastrointestinal tract.
Keywords: Products; Flour; Digestion